PENERAPAN MEDIA TEKA-TEKI SILANG PADA MATERI KOLOID UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Uci Sulfia; Habibati Habibati (Program Studi Magister Pendidikan IPA Program Pascasarjana Universitas Syiah Kuala, 2018)
Abstract. Research on "Application of Cross Puzzle Media on the Material of Colloid Systems to Improve Learning Outcomes of Students Grade XI SMA Negeri 3 Banda Aceh". This study aims to determine learning results, activities and responses of learners after studying the materials colloid system with the implementation of TTS media. This study used a qualitative approach and the type of experimental research. Subjects in this study were students of class XI MIA 7 as an experimental class and class XI MIA 6 as the control class. Data collected by observation activities, attitudes, the TTS media, the LKPD, tests and questionnaires. The instruments used were observation of sheet activities, attitudes, the TTS media, the LKPD and test questions as well responses of learners. The results showed that the classical completeness learning outcomes of students in the experimental class knowledge aspect 84.37% higher than the control class that is 43.75%. The average value of the activity of students in the first meeting and the second using the TTS media is 91.66% greater than the control class using the LKPD is 75.42%. Positive response of learners to use the TTS media obtained by percentage of 92.27% is included in the excellent. Based on the results of this study concluded that the application of the TTS media the materials colloid system can accomplish the learning outcomes of students, increases the activity of learners, and give a positive response to the learning activities. Keywords: TTS, learning outcomes, activities, colloids.